Analisis Hukum Islam terhadap Praktik Pinjaman Online Berbasis Bunga di Indonesia - Abu Bakar; Halimatus Sa’diyah (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2026)
The phenomenon of interest-based online loans in Indonesia has grown rapidly in line with the increasing use of financial technology (fintech). While such services provide quick access to financing, they often generate serious problems, including excessive interest rates, compounded penalties, and unethical debt collection practices that harm borrowers. From the perspective of Islamic law, these practices raise concern as they potentially involve prohibited elements. This study aims to analyze the practice of interest-based online loans in light of Islamic legal principles, particularly regarding the prohibition of riba, gharar, and dharar. This research employs a qualitative normative method using library research, referring to the Qur’an, Hadith, classical fiqh, fatwas of the Indonesian Ulema Council (MUI), and relevant financial regulations in Indonesia. The findings reveal that the interest charged in online lending is classified as riba, which is explicitly prohibited in the Qur’an and Hadith. Furthermore, the imposition of unclear additional fees reflects elements of gharar, while the harmful socio-economic impacts on vulnerable groups demonstrate dharar. Therefore, interest-based online loans are inconsistent with Islamic law. As an alternative, this study recommends the development of sharia-compliant fintech platforms based on legitimate contracts such as qardh hasan, murabahah, and wakalah, which ensure fairness, transparency, and alignment with the objectives of Islamic law (maqāṣid al-sharī‘ah).